1. Hu S, Sprintall J, Guan C, et al. Deep-reaching acceleration of global mean ocean circulation over the past two decades. Sci Adv. 2020;6(6):eaax7727. - Shijian Hu; Wenju Cai (TheScienceBreaker, 2020)
Lupus nephritis (LN), a severe manifestation of systemic lupus erythematosus (SLE), is a heterogeneous disease driven by diverse immune and tissue cell types. We obtained 538,194 single-cell and 142,881 single-nuclear profiles from kidney biopsies of 155 patients with LN and 30 preimplantation transplant biopsy controls, along with 327,326 single-cell blood profiles. We characterized key stromal and immune cell types and cell states; moreover, we distinguished cell states that were tissue specific from those that were also present in the blood. We observed that LN pathological features were associated with particular cell states. For example, after controlling for the effects of chronic tissue damage, we observed that expansion of glomerular and scar-associated macrophage populations correlated with increasing inflammatory disease activity. Scar-associated macrophages appear to drive LN fibrosis and, in active disease, infiltrate the glomeruli more than other myeloid cells. These observations support that therapeutic targeting of myeloid populations may offer a strategy to prevent renal inflammation and ongoing kidney damage in LN.